Results of Complex Surgical Treatment of Appendicular Peritonitis in Girls - Davranov, Bobir Latibovich; Yusupov, Shukhrat Abdurasulovich; Makhmatkulov, Khomidullo Gaybullaevich (RA Journal of Applied Research, 2022)
Acute peritonitis is one of the biggest sequela of abdominal cavity organ diseases. During puberty girls are especially vulnerable forasmuch as peritonitis registered in this age may lead to chronic salpingitis, adhesive process in cavum abdominis and connected with it tubal-peritonial infertility in 25-33% of cases. The implementation of the suggested surgical treatment and aftercare measures among girls with appendicular peritonitis allows to reduce the risk of adhesive process development from 21, 4% to 8,1% and the quantity of relaparatomy from 5,1% to 0.5%.